Moral challenges of research on embryos in pre-implantation genetic diagnosis and IVF - Naseri, Leila; Abbasi, Mahmoud; Hashemi, Mehrdad (Archives of Advances in Biosciences, 2018)
Purposes of pre-implantation genetic diagnosis (PGD) include screening for single gene mutations for late onset disorders or susceptibility to cancer. The problematic issue is that PGD is to produce a healthy baby, causing the destruction of some embryos that have been transferred by in vitro fertilization (IVF). Some PGD embryos may be discarded because they are excess to the woman or couples’ goal for family creation, and have been diagnosed as being affected by a particular genetic condition that woman/couple wish to avoid. So, the controversial issue is the destruction of embryos as a consequence of fertility treatment that raises questions on whether the moral status of an embryo of 3 days is the same as that of a born, living adult human being.